Hubungan Status Gizi Dengan Perkembangan Anak Usia 3 – 4 Tahun - Rosyidah, Rafhani; Aprilia, Puput (Journal of Issues in Midwifery, 2017)
BSTRACT Development is the increasing ability, body functions, and structures more complex in regular patterns and can be predicted as a result in the process of maturation. One that affects child development is nutritional status. From the preliminary data, it was found 15.9% had less nutrition in 2015 in Sidoarjo regency than the government target of 15% .The purpose of this study was to know the relationship of nutritional status with the development of children aged 3-4 years.The research design used with analytic with cross sectional approach. Data collection using KPSP to assess child development, and KMS to assess nutritional status. A sample size of 31 children aged 3-4 years. Data is presented with frequency table and cross tabulation, then analyzed by using chi square test with significance level α = 0,05. From the test results obtained p value = 0.034. Children whose development corresponds to more good nutritional status (86.7%), compared with less nutritional status (43.7%). And the dubious development of more nutritional status is less (56,3%), compared to good nutrition status (13,3%).The conclusion of this research is there is relationship of nutritional status with the development of children aged 3-4 years. Parents should strive to meet the child's nutrition for good development.